The Role of Self-Awareness as a Mediator in the Relationship Between Spiritual Intelligence and Anti-Plagiarism Behavior Among Muslim Students - Tri Handoyo; Syukri Amin; Dedy Novriadi; Rifai’i, Rifai’i; N. Baskautshar (Journal of Social and Humanities, 2023)
This study examines the mediating role of self-awareness in the relationship between spiritual intelligence and anti-plagiarism behavior among Muslim students in Indonesia. A quantitative approach using structural equation modeling (SEM) was employed with a sample of 300 students from Islamic higher education institutions. The findings demonstrate that spiritual intelligence significantly influences anti-plagiarism behavior both directly (β = 0.28, p < 0.01) and indirectly through self-awareness as a partial mediator (β = 0.234, p < 0.001). The mediation effect accounts for 45.5% of the total effect, indicating that self-awareness serves as a crucial psychological mechanism in translating spiritual values into ethical academic conduct. The model explains 41% of the variance in anti-plagiarism behavior, highlighting the significance of psycho-spiritual factors in academic integrity. These results challenge conventional plagiarism prevention approaches and advocate for holistic character development strategies that integrate spiritual intelligence and self-awareness cultivation within educational frameworks.